THE POWER MESSAGE OF THE DON JUAN FIGURE - Stankevičiūtė, Kristina (Verbum, 2015)
Don Juan, one of the most popular cultural figures in the Western civilization, has deserved the attention of philosophers relatively recently. Postmodern and post-structuralist reflections on the issues related to the character of Don Juan refer to the figure as a ready-made construct whose implications and meanings are well-established. It indicates that the Don Juan figure represents a certain cultural phenomenon in social (and philosophical) consciousness. That image is an instrument of reflection on the social perception of human sexuality in general, and attempts to systematize and govern it in particular. The article suggests a reading of the Don Juan figure within the frames of Michel Foucault’s theory of power claiming that the meaning of the character of Don Juan lies in its power-based relations with his environment. Seen in the Foucauldian light, Don Juan is an instrument of the system of surveillance over the ‘law of marriage’, to quote Foucault; he is the one who disobeys the discipline of the social system, and seems to have the privilege of being exempt from its requirements. The analysis of the three power-based relations (Don Juan’s domination over the society, over the women whom he violates, and over his own discourse) leads to the conclusion that Don Juan is a political power-figure, because he acts as an instrument of surveillance over the social male-female relationship. Yet the story of Don Juan also raises the problem of an individual against an authority, and the limits of a system as opposed to individual freedom. Along with being an ‘irritator’, a certain ‘tester’ of the limits of the social tolerance to individual violations of the accepted moral laws, Don Juan becomes the symbolical figure that embodies the inherent human need to transgress the accepted norms, to explore the limits of freedom. Don Juan’s seduction becomes an invitation to partake of his liberty, to spend a moment in an unrestricted existence, in the primeval freedom of self-enjoyment. At the same time, however, the seduction process performed by Don Juan launches the inner censorship, or the inner surveillance apparatus of every individual – the female victim, her male protector (father, brother or any other), other members of the Don Juan’s society, as well as male and female members of his audience (i.e. the spectators, or the readers). That is, the article suggests, the power message that the Don Juan figure broadcasts to the culture it acts in.